Traditional cultural heritage artefacts in the sultanate palace of Melaka: the benefits of sus-taining cultural values through the furniture design and development process in related fields in Malaysia / Siti Nurmasturah Harun...[et al.] - Harun, Siti Nurmasturah; Shaharudin, Haszlin; Ahmad, Mohammad Azroll; Bonollo, Elivio; Wan Omar, Wan Noor Faaizah (Universiti Teknologi MARA, Kedah, 2020)
This paper reports on the first part of an extensive theoretical and empirical investigation of heritage elements in the context of world culture. The main objective of this research is to contribute towards sustaining cultural heritage values, in Malaysia, though furniture design and development process. This research focuses on a study of Melaka’s traditional cultural elements in the Sultanate Palace, while being mindful of the growth of modernization in Malaysia. Notably, Malaysia is proud to have a few places listed as World Heritage Sites by UNESCO. An understanding of the importance of sustaining/ maintaining cultural heritage through furniture design is assumed to be broadly related to the thinking and problem-solving methods of designer-makers as reflected overtly in their stepby- step solutions to furniture design problems which incorporate cultural values. A basic research has been carried out to study how an appreciation of historical heritage and traditional cultural furniture elements began in a society. The research methodology applied in this research is based on qualitative methods involving interviews and observations with a relevant group of designer-makers. As description of historical artifacts of the Melaka Sultanate are rarely found in literature, the historical relics of the Melaka Sultanate Palace have been rebuilt from the viewpoint of the literature “Sulalatus Salatin”, in order to reminisce on the greatness of Melaka and the uniqueness of the Malay traditional culture in the 15th century. This paper will show that it is possible to incorporate and adapt unique cultural elements into contemporary furniture design; moreover, this outcome will facilitate the building up of reference materials relevant to design education as well as for heritage organization purposes.